The Effect Of Third Party Funds, CAR, NPL On Credit Distribution Company Listed on BEI - Siti Hanifa Sandri; Siti Samsiah; Dewi Puspita Sari (Akuntansi & Ekonomika, 2019)
The purpose of this study is to examine the effect of third party funds, capital adequacy ratios, and non-performing loans on lending. The population in this study is commercial banks that have gone public in Indonesia in the 2014-2017 period as many as 19 banks. The entire population in this study was sampled. The data used in this study are secondary data, namely the company's 2014-2017 financial statements. The processing method used is multiple linear regression analysis. Based on the results of the study, it can be concluded that the variables of third party funds and capital adequacy ratio have a positive effect on lending. While the non-performing loan variable has no effect on lending.